2016
DOI: 10.12669/pjms.326.11436
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing musculoskeletal system discomforts and risk factors in computer-using office workers

Abstract: Objective:This study analyzed the prevalence of work-related computer-user musculoskeletal discomforts, personal and computer-related risk factors.Methods:A cross-sectional survey on 395 office workers was made between July-September 2015. Musculoskeletal symptoms and risk factors were evaluated for participants’ demographics and job attributes on the 21-item questionnaire and the Turkish-Cornell Musculoskeletal Discomfort Questionnaire.Results:Participants reported musculoskeletal symptoms in the neck (67.85%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
51
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 13 publications
15
51
1
13
Order By: Relevance
“…This prevalence was slightly higher compared to a study conducted by Mahmud et al [19], in Malaysia among computer users where the upper and lower back due to improper alignment in front of a computer for long duration was 38.9%. However, it was lower compared to a study conducted in Manisa, Turkey among computer using office workers which revealed 66.3% [20]. Generally in the literature, back pain prevalence ranges from 37.3% [21] to 70-85% [22].…”
Section: Discussionmentioning
confidence: 72%
“…This prevalence was slightly higher compared to a study conducted by Mahmud et al [19], in Malaysia among computer users where the upper and lower back due to improper alignment in front of a computer for long duration was 38.9%. However, it was lower compared to a study conducted in Manisa, Turkey among computer using office workers which revealed 66.3% [20]. Generally in the literature, back pain prevalence ranges from 37.3% [21] to 70-85% [22].…”
Section: Discussionmentioning
confidence: 72%
“…Kumah et al (2016) in another study also reported that 85 % of the respondents experienced musculoskeletal problems in the neck, back and shoulder, which could be attributed to the ergonomic deficiencies at the workstations. Ardahan and Simsek (2016) in a study on musculoskeletal disorders in computer users reported that participants reported musculoskeletal symptoms most commonly in the neck (67.85%), upper back (66.33%), lower back (59.49%), right shoulder (45.32%) and left shoulder (43.54%). Table 3 also reveals the frequency of body pain felt by respondents and results show that majority (88.32%) of the girls, as well as boys, felt pain in the neck while working on computer/laptop sometimes as evident from the mean score of 2.10 and 2.07 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term usage of computers, working at a desk and sitting for a long time in a chair in workplaces are the main reasons playing a role in the musculoskeletal system disorders of office workers. Office workers are forming a very important part of the risk group for musculoskeletal system disorders as they are spending long working hours in front of a computer (Ardahan and Simsek., 2016). The prevalence of work-related musculoskeletal disorders (WMSD"s) is increasing among computer users throughout the world (Luis et al, 2003;Arun, 2013) and increase in the frequency of symptoms through the years has been observed with the rapid development of computer technologies and ever-increasing usage of computers (Ulusam et al, 2015 andPiranveyseh, 2016) .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of computers in the workplace has also led to the introduction of a specific category of work-related musculoskeletal disorders (MSDs) for office-based workers. MSDs procured in office-based workplaces can become particularly debilitating, since these categories of disorders principally cause distress to sensitive anatomical regions such as the neck, the lower back, but also the shoulders and the extremities of the upper limbs [15][16][17][18][19]. Symptoms can vary, but the occurrence of chronic pain and motor dysfunction are quite well-established [16].…”
Section: Highlight By Alessandro Castorinamentioning
confidence: 99%
“…Symptoms can vary, but the occurrence of chronic pain and motor dysfunction are quite well-established [16]. The manifestations seem to be triggered either by isolated or combined micro traumas to muscles, tendons, joints, and nerves [15,19]. Often, the causes are attributed to poor habits in the workplace, such as repeated wrist movements (as in the act of dragging the mouse or clicking its buttons), and can also be the consequence of inappropriate posture and/or sitting in front of an office computer for extensive periods of time.…”
Section: Highlight By Alessandro Castorinamentioning
confidence: 99%